Digital Transformation in Islamic Banking: Its Impact on Islamic Economics in Indonesia - badawi, afif (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2025)
The digital transformation of the banking sector has significantly reshaped financial services globally, with Islamic banking in Indonesia also embracing these changes. This paper examines the impact of digital transformation on Islamic banking and its broader effects on Islamic economics in Indonesia. With the integration of technologies such as mobile banking, blockchain, and digital platforms, Islamic banks in Indonesia are enhancing financial inclusion, improving customer experience, and offering innovative Shariah-compliant financial products. This study highlights the role of digital transformation in increasing accessibility to financial services for underserved populations while adhering to Islamic economic principles. However, challenges such as infrastructure limitations, cybersecurity concerns, and ensuring Shariah compliance remain key considerations. The findings suggest that digital transformation has the potential to drive growth in Islamic banking and contribute to the development of a more inclusive and ethical economy. The paper concludes by emphasizing the need for continuous innovation and careful alignment with Shariah principles to ensure that digital technologies positively impact the Islamic financial sector and economy in Indonesia.